CERN: A European laboratory for a global project. (May 2015) - Voss, Rüdiger
Abstract: In the most important shift of paradigm of its membership rules in 60 years, CERN in 2010 introduced a policy of "Geographical Enlargement" which for the first time opened the door for membership of non-European States in the Organization. This short article reviews briefly the history of CERN's membership rules, discusses the rationale behind the new policy, its relationship with the emerging global roadmap of particle physics, and gives a short overview of the status of the enlargement process.